The recruiter's excitement – features of thoracic vibrations during the honey bee's waggle dance related to food source profitability - Hrncir, Michael (2011)
The honey bee's waggle dance constitutes a remarkable example of an efficient code allowing social exploitation of available feeding sites. In addition to indicating the position (distance, direction) of a food patch, both the occurrence and frequency of the dances depend on the profitability of the exploited resource (sugar concentration, solution flow rate). During the waggle dance, successful foragers generate pulsed thoracic vibrations that putatively serve as a source of different kinds of information for hive bees, who cannot visually decode dances in the darkness of the hive. In the present study, we asked whether these vibrations are a reliable estimator of the excitement of the dancer when food profitability changes in terms of both sugar concentration and solution flow rate. The probability of producing thoracic vibrations as well as several features related to their intensity during the waggle phase (pulse duration, velocity amplitude, duty cycle) increased with both these profitability variables. The number of vibratory pulses, however, was independent of sugar concentration and reward rate exploited. Thus, pulse number could indeed be used by dance followers as reliable information about food source distance, as suggested in previous studies. The variability of the dancer's thoracic vibrations in relation to changes in food profitability suggests their role as an indicator of the recruiter's motivational state. Hence, the vibrations could make an important contribution to forager reactivation and, consequently, to the organisation of collective foraging processes in honey bees.